Spatial Ability Explains the Male Advantage in Approximate Arithmetic - Wei, Wei; Chen, Chuansheng; Zhou, Xinlin (Frontiers in Psychology, 2016)
Previous research has shown that females consistently outperform males in exact arithmetic, perhaps due to the former’s advantage in language processing. Much less is known about gender difference in approximate arithmetic. Given that approximate arithmetic is highly associated with visuospatial processing and there is a male advantage in visuospatial processing, we hypothesized that males would perform better than females in approximate arithmetic. In two experiments (496 children in Experiment 1 and 554 college students in Experiment 2), we found that males showed better performance in approximate arithmetic. Furthermore, gender differences in approximate were accounted for by gender differences in spatial ability.